Rational design of three bifunctional MOFs for photocatalysis degradation and selective adsorption of wastewater organic dyes removal. (15th November 2020) - Zhang, Xiaoyin; Zong, Ziao; Zhang, Xia; Zhang, Dongmei; Luo, Qingdan; Bi, Caifeng; Fan, Yuhua
Graphical abstract: Highlights: Three MOFs based on based on transition metals have been synthesized. The title MOFs exhibit both good photocatalytic degradation and adsorption for organic dyes removal capability for waste water treatment. The tentative mechanism has been discussed. Abstract: Three metal–organic frameworks (MOFs) based on transition metals, namely[Cd(HL)(tib)(H2 O)]·1·.5H2 O